RESEARCH OF THE IMPACT OF THE DOWNSIZINGS ON ENTERPRISES OF VARIOUS SPHERES OF ECONOMICS - Сотнікова, Ю. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2014)
The stage research of the impact of downsizings on enterprises has been conducted by assessing the state enterprises before the implementing procedures of downsizing, identifying the reasons for downsizing for the enterprises, the assessment of business after the implementation of downsizing procedures, and as a result, the definition of areas of work with the redundant workers that has been based on the methods of questioning.